Emerging pharmaceutical therapeutics and delivery technologies for osteoarthritis therapy - Shentu, Cheng-Yu; Yan, Ge; Xu, Dong-Chen; Chen, Yong; Peng, Li-Hua (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is one of the most common joint degenerative diseases in the world. At present, the management of OA depends on the lifestyle modification and joint replacement surgery, with the lifespan of prosthesis quite limited yet. Effective drug treatment of OA is essential. However, the current drugs, such as the non-steroidal anti-inflammatory drugs and acetaminophen, as well as glucosamine, chondroitin sulfate, hyaluronic acid, are accompanied by obvious side effects, with the therapeutic efficacy to be enhanced. Recently, novel reagents such as IL-1 antagonists and nerve growth factor inhibitors have entered clinical trials. Moreover, increasing evidence demonstrated that active ingredients of natural plants have great potential for treating OA. Meanwhile, the use of novel drug delivery strategies may overcome the shortcomings of conventional preparations and enhance the bioavailability of drugs, as well as decrease the side effects significantly. This review therefore summarizes the pathological mechanisms, management strategies, and research progress in the drug molecules including the newly identified active ingredient derived from medicinal plants for OA therapy, with the drug delivery technologies also summarized, with the expectation to provide the summary and outlook for developing the next generation of drugs and preparations for OA therapy.